2016
DOI: 10.1038/srep20211
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of body mass index and emotional-behavioral functioning of underweight children: A longitudinal study

Abstract: Although several studies have addressed developmental trajectories from childhood to adolescence of internalizing/externalizing problems, limited attention has been given to underweight children. Two groups were recruited for this study from a community sample: underweight (Ug, N = 80, 50% female) and normal weight (NWg, N = 80, 50% female) to examine the developmental trajectories of body mass index and emotional-behavioral functioning of underweight children from the age two years, and their risk of eating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 81 publications
(76 reference statements)
3
22
0
Order By: Relevance
“…Overall, our findings are consistent with previous research in showing high rates of psychopathological symptoms in children of parents with psychiatric diagnosis, suggesting a negative effect of parental eating disorders on their offspring's mental health (Cerniglia et al, 2014;Cimino et al, 2015;Cimino et al, 2016a 110 relationship between parents diagnosed with BED and their children at 36 months, our data are consistent with those of previous studies that argued that psychiatric disease in parents lead to offspring's uneasiness, which could crystalize into early psychopathological symptoms (Cimino et al, 2015;Cimino et al, 2016a). Even more so, findings in the current study turn out to be very important in relation to child mental health, since early children's emotional and behavioural difficulties in the first years of life tend to increase overtime (Ammaniti, Lucarelli, Cimino, D'Olimpio & Chatoor, 2012;Cimino et al, 2016b;Cimino et al, 2015).…”
Section: Resultssupporting
confidence: 82%
“…Overall, our findings are consistent with previous research in showing high rates of psychopathological symptoms in children of parents with psychiatric diagnosis, suggesting a negative effect of parental eating disorders on their offspring's mental health (Cerniglia et al, 2014;Cimino et al, 2015;Cimino et al, 2016a 110 relationship between parents diagnosed with BED and their children at 36 months, our data are consistent with those of previous studies that argued that psychiatric disease in parents lead to offspring's uneasiness, which could crystalize into early psychopathological symptoms (Cimino et al, 2015;Cimino et al, 2016a). Even more so, findings in the current study turn out to be very important in relation to child mental health, since early children's emotional and behavioural difficulties in the first years of life tend to increase overtime (Ammaniti, Lucarelli, Cimino, D'Olimpio & Chatoor, 2012;Cimino et al, 2016b;Cimino et al, 2015).…”
Section: Resultssupporting
confidence: 82%
“…aggression and hyperactivity) (Achenbach & Rescorla 2000). In terms of predictive implications, in line with the DP framework, recent studies highlight that the early onset of emotional-behavioural problems during childhood can imply several difficulties across the following stages of life, such as adolescence and adulthood (Ammaniti et al, 2012;Cimino et al, 2016). The earlier difficulties are identified, the earlier it is possible to plan support and intervention programs.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, it has been shown that children born at very low gestational age are at risk of linguistic disorders in their first years of life ( Capobianco et al ., 2010; Cimino et al ., 2016). The present longitudinal study aimed at analyzing communication and language abilities in preterm children during their second year of life, through a standardized questionnaire for parents, the “Primo Vocabolario del Bambino” (Caselli et al ., 2015) (PVB, Italian version of “MacArthur-Bates”, age 8–36 months) with particular attention to communication abilities that are predictors of the first verbal skills at 3 years ( Pizzuto & Capobianco, 2008; Capobianco et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%